Potential Development Management of Students in Islam - MOCH CHARIS HIDAYAT; CHOIRUL MAHFUD (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2019)
This study aimed to investigate and describe the management of developing potential students based on Islamic views. This study used a qualitative method with a case study approach. The subjects of the research were Madrasah supervisors, Madrasah headmasters, and the teachers. The results of the study showed that the development of potential students when referring to the objectives of national education in particular and development, in general, is to create